(3Lfi GdLfGSs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjf EUWai gPG GdcJGH CdaJg ai CbSGe GdLfGS GdJi ESJNQLJgG hMVQJgG hde CSHb Edi Pdc hhUdJgG Edi fMh GdCQHYeGFI bSe hCcKQJ ef EHQGO ThGgOgG GdbQBfjI s
(3BNQgG (B:s
(3hce Hg UM eYbd hdGM dg fhQ h fGQ ef GdJhajb hGdgee hGdMeO ddg hMOg hUdi Gddg hSde Ydi SjOfG eMeO hYdi Bdg hUMHg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B607s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdHdGZIs